Angiotensin Converting Enzyme Inhibitors and the Risk of Lung Cancer – New Scientific Evidences or Another Example of “Pseudo-Evidence” Medicine? - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии, 2019)
The quality of the database analysis that led to the conclusion that angiotensin converting enzyme inhibitors contribute to the development of lung cancer is analyzed. The author notes that the analysis of the potential risk from taking these drugs is possible only if it is related to the proven positive effect of these drugs on the prognosis of life in certain categories of patients, primarily with chronic heart failure and a history of acute myocardial infarction. Attention is drawn to the methodological errors of the study, putting the main conclusion of the analysis into question.